Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.15446/esrj.v21n3.65216
|View full text |Cite
|
Sign up to set email alerts
|

PNN-based Rockburst Prediction Model and Its Applications

Abstract: Rock burst is one of main engineering geological problems greatly threatening the safety of construction. Prediction of rock burst is always an important issue concerning the safety of workers and equipments in tunnels. In this paper, a novel PNN-based rock burst prediction model is proposed to determine whether rock burst will happen in the underground rock projects and how much the intensity of rock burst is. The probabilistic neural network (PNN) is developed based on Bayesian criteria of multivariate patte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…For example, neural networks, fuzzy comprehensive evaluation methods, analytic hierarchy processes, random forest methods, Bayesian models, support vector machines, cloud models, multivariate time series reconstruction, abstraction ant colony clustering algorithms, etc. [8,[27][28][29][30][31][32][33][34], have been used to study rock mechanics problems. Therefore, we can try to predict and can warn of rockburst risk by using the intelligent method and MS data together.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, neural networks, fuzzy comprehensive evaluation methods, analytic hierarchy processes, random forest methods, Bayesian models, support vector machines, cloud models, multivariate time series reconstruction, abstraction ant colony clustering algorithms, etc. [8,[27][28][29][30][31][32][33][34], have been used to study rock mechanics problems. Therefore, we can try to predict and can warn of rockburst risk by using the intelligent method and MS data together.…”
Section: Introductionmentioning
confidence: 99%
“…Feng et al [8] used MS information and a neural network to predict rockburst risk in deep tunnels of the Jinping II hydropower project. Zhou et al [34] successfully predicted the risk of rockburst in the construction of Tongyu and Qinling tunnels by using the probabilistic neural network (PNN) model; however, when using PNN for rockburst prediction, if the dimension of variables in input samples is large or there is a correlation between the variables, the prediction performance will be reduced [35], and the parameter smoothing factor in PNN affects the classification performance [36].…”
Section: Introductionmentioning
confidence: 99%
“…Five rockburst events in two different tunnel projects were predicted by the AdaBoost model. e field data were collected from available literature, including the Duoxiongla tunnel [58] and Anlu tunnel [59]. e prediction outcomes are summarized in Table 6, indicating that the rock burst intensity was predicted correctly for all cases.…”
Section: Applications In Real-world Rockburst Prediction Two Real-wor...mentioning
confidence: 98%
“…The prediction results indicated that the PCA-GRNN model and PCA-RBF model showed more excellent network performances and higher prediction accuracy and generalization ability. Zhou and Wang [19] developed the probabilistic neural network (PNN) based on Bayesian criteria of multivariate pattern classification. Afraei et al [20] developed intelligent classification models for rock burst prediction by using five widespread techniques including artificial neural network techniques; different classification models are trained and tested with the same corresponding datasets to evaluate and compare their performances in the similar conditions.…”
Section: Introductionmentioning
confidence: 99%